Integrated physical training: An experimental study on the overall performance of basketball players - Oki Candra; Ahmad Rahmadani; Toktong Parulian; Putri Wahyuni; Siti Hannariah Mansor; Satrio Satrio (Journal of Coaching and Sports Science, 2026)
Background: Basketball performance requires integrating multiple physical components, including strength, speed, agility, flexibility, and endurance. However, conventional training programs often emphasize isolated components, limiting optimal performance development. An integrated training approach is therefore needed to address the multidimensional physical demands of basketball. Aims: Evaluate the effectiveness of an Integrated Physical Training (IPT) program in improving overall physical performance in basketball players, focusing on key components: strength, speed, agility, flexibility, and endurance. Methods: A quasi-experimental pre-test–post-test control group design was employed. Twenty-four male basketball players were randomly assigned to an experimental group and a control group. The intervention was conducted over 12 sessions (three sessions per week). Physical performance was assessed using a standardized fitness test battery covering strength, speed, agility, flexibility, and endurance. Data were analyzed using inferential statistics and effect size (Cohen’s d). Result: The IPT group demonstrated significant improvements (p < 0.05) across all physical performance variables compared to the control group. Effect sizes ranged from large to very large (Cohen’s d= 1.26–3.00), indicating substantial multidimensional performance gains. Conclusion: Integrated Physical Training (IPT) is more effective than conventional training in improving overall physical performance in basketball players. This approach is recommended as a comprehensive training model to optimize sport-specific physical adaptations.